Non Seminomatous Mixed Germ Cell Tumor of Testis with a Large Abdominal and Retroperitoneal Extension: A Case Report - Kayastha, Rumita; Pradhan, S; Acharya, R; Aryal, M; Shrestha, A; Tuladhar, AS (Nepal Medical College Journal, 2020)
Primary testicular germ cell tumors (PGCT) can be classified as seminomatous and non-seminomatous germ-cell tumor (NSGCT) types. Mixed germ cell tumors (MGCT), a subtype of NSGCT, contain more than one germ cell components. Here, we present a rare case of a MGCT composed of yolk sack tumor and teratoma which had a continuous large abdominal and retroperitoneal extension. A 43 years old male presented with complaints of discomfort and swelling over the right inguinoscrotal region. Ultrasonography (USG) showed a large ill-defined heteroechoic mass in the right inguinoscrotal region with vascularity and without separate visualization of right testis. Subsequent contrast enhanced Computed Tomography (CT) showed large enhancing mass in the right scrotal sac which was continuous with large abdominopelvic and retroperitoneal mass through the right inguinal canal. Tru-Cut biopsy of the scrotal mass showed MGCT with yolk sac and teratoma component. Patient underwent 6 cycles of chemotherapy followed by Right Radical Inguinal Orchidectomy.